MONITORING THE EFFECTS OF EXCESSIVE USE OF CHEMICAL FERTILIZERS ON UNDERGROUND WATERS BY USING THE GIS TECHNIQUE - BIALI, Gabriela (Studia Universitatis Babeș-Bolyai Geographia, 2016)
Monitoring the Effects of Excessive Use of Chemical Fertilizers on Underground Waters by Using the GIS Technique. This paper highlights the increase of nitrates and nitrites content in the underground waters, in correlation with the levitation to the underground of the nitrogen quantity on the agricultural lands, by using a modelling method through the GIS technique. The research is conducted for the underground waters of an area of Prut River catchment, and for the assessment of NO2, NO3 concentration, water samples are taken from a limited number of boreholes (44 boreholes). These boreholes are randomly distributed in the area and only some pieces of information are acquired from the laboratory tests. Based on this source data, by means of an interpolation method under software Surfer 8.1, the maps of NO2, NO3 concentration distribution were created. The spatialisation is made on 1880 cells and the results set out herein are at the level of a 2015 survey year. The Romanian Law on fresh water sets out that although the nitrites and nitrates are within the admitted maximum limits 0.5 mg/l and 50 mg/l, respectively, another indicator should also be taken into consideration: Thus, in the application, the mathematical modelling generated a map of the above mentioned indicator distribution. One can notice that, under certain circumstances, although the NO2 and NO3 indicators are within the admitted maximum limits, this indicator is still exceeded. This leads to the conclusion that in certain areas of the analyzed region there is significant chemical pollution, fact that leads to safety actions concerning the use of well water.